2007
DOI: 10.1128/iai.00072-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transferrin-Binding Domains in TbpB Expressed by Neisseria gonorrhoeae

Abstract: The transferrin iron acquisition system of Neisseria gonorrhoeae is necessary for iron uptake from transferrin in the human host and requires the participation of two distinct proteins: TbpA and TbpB. TbpA is a TonB-dependent outer membrane transporter responsible for the transport of iron into the cell. TbpB is a lipid-modified protein, for which a precise role in receptor function has not yet been elucidated. These receptor complex proteins show promise as vaccine candidates; therefore, it is important to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Tf-iron uptake assays were performed as described previously (32)(33)(34)(35). Briefly, apo-human Tf (Sigma) was saturated to 20% with 55 Fe (Perkin-Elmer).…”
Section: Figmentioning
confidence: 99%
“…Tf-iron uptake assays were performed as described previously (32)(33)(34)(35). Briefly, apo-human Tf (Sigma) was saturated to 20% with 55 Fe (Perkin-Elmer).…”
Section: Figmentioning
confidence: 99%
“…Apo-and holo-Tf forms have different affinities for the bacterial Tbp receptors. Unlike TbpA, the TbpBs have a strong preference for binding to the holo-form of Tf (20 -23), which suggests that TbpB may play a role in efficient capture of the holo-form of Tf (24,25). For the Actinobacillus spp., in vitro studies have shown that a TbpBdeficient strain could utilize Tf-bound iron, but was avirulent (26).…”
mentioning
confidence: 99%
“…This potential for diverse receptor-Tf recognition mechanisms provides a rationale for characterizing Tf-TbpB interactions across multiple variants. The sequence heterogeneity for TbpB proteins in particular is considerable, with 47-82% sequence identity observed in variants from a cross-section of pathogenic strains (25,27). Therefore, this study seeks to determine the impact of such heterogeneity on the interaction with Tf, from the perspective of Tf.…”
mentioning
confidence: 99%
“…TbpB was previously demonstrated to be lipidated (16) and fully surface exposed (35), similar to other neisserial lipoproteins, as well as lipoproteins of several other Gram-negative bacteria, such as Klebsiella, Bordetella, and Borrelia spp. (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, lipoprotein transport has been well characterized, with the periplasmic Lol system shuttling lipoproteins destined for the outer membrane to their proper location (39). However, unlike the majority of E. coli lipoproteins, which tend to be oriented toward the periplasm, many lipoproteins produced by the gonococcus and other related species are oriented toward the extracellular milieu (35,38). In addition, while N. gonorrhoeae possesses homologues of some of the Lol proteins, the chromosome does not encode a LolE homologue.…”
Section: Discussionmentioning
confidence: 99%